Placebo Analgesia Reduces Costly Prosocial Helping to Lower Another Person's Pain. (November 2022) - Hartmann, Helena; Forbes, Paul A. G.; Rütgen, Markus; Lamm, Claus
Painkiller administration lowers pain empathy, but whether this also reduces prosocial behavior is unknown. In this preregistered study, we investigated whether inducing analgesia through a placebo painkiller reduced effortful helping. When given the opportunity to reduce the pain of another person, individuals experiencing placebo analgesia ( n = 45 adults from Austria; 21 male, 24 female) made fewer prosocial choices at the lowest helping level and exerted less physical effort when helping, compared with controls whose pain sensitivity was unaltered ( n = 45; 21 male, 24 female). Self-reported empathic unpleasantness positively correlated with prosocial choices across the whole sample. While not replicating group differences in empathy, a mediation analysis revealed that the level of unpleasantness to other people's pain fully mediated the effect of placebo analgesia on prosocial choices. Given the importance of prosociality for social cohesion, these findings have broad potential implications both for individuals under the influence of painkillers and for society at large.